Revealing the Role, Mechanism, and Impact of AlF3 Coatings on the Interphase of Silicon Thin Film Anodes (Adv. Energy Mater. 41/2022). Issue 41 (3rd November 2022) - Adhitama, Egy; van Wickeren, Stefan; Neuhaus, Kerstin; Frankenstein, Lars; Demelash, Feleke; Javed, Atif; Haneke, Lukas; Nowak, Sascha; Winter, Martin; Gomez‐Martin, Aurora; Placke, Tobias
Abstract : Solid Electrolyte Interphases In article number 2201859, Aurora Gomez‐Martin, Tobias Placke, and co‐workers discuss the role, mechanism, and impact of AlF3 coating on Si thin film anodes. The observations were done in different (de‐)lithiation states. AlF3 transforms to Li‐Al‐F compounds with higher ionic conductivity, thus, increasing cycling stability. This study provides significant insights into the solid electrolyte interphase behavior with regard to the functional coating layer.